Avaliação da radiação UVC, processos UV/H2O2 e fotofenton na degradação do agrotóxico clorpirifós com acompanhamento da ecotoxidade - Lima, Rubia Matos de (2017)
Anthropogenic activities, such as agriculture, have led to a loss of ecosystem quality. Due to physical, chemical and biological processes that occur, after a pesticide application, much of it does not reach its main goal and ends up contaminating the environment. Chlorpyrifos is one of the most widely used pesticide in the world due to its broad spectrum of performance. The presence of pesticides in potable water sources indicates the inefficiency in the conventional water treatment processes and an alternative are the advanced oxidation processes (AOPs). Despite the high removal rates obtained with AOPs, there is also need an evaluation of the treatments’ efficiency through ecotoxicity assays. The aim of this work was to evaluate the UVC, UV/H2O2 and photo-Fenton processes in the degradation of the chlorpyrifos and evaluate ecotoxicity.The degradation were performed in bench scale using reactors and as a radiation source a high pressure lamp of mercury vapor (125 W). Chlorpyrifos concentration was monitored by HPLC-DAD.The organisms used in the ecotoxicity assays were L. sativa, D. magna and A. aegypti. An evaluation of the ecotoxicity of organic solvents in aqueous solution through assays with L. sativa and D. magna found that the most indicated solvent for solubilization of chlorpyrifos is acetone. Chlorpyrifos quantification after degradation was performed with a liquid-liquid phase extraction reaching recovery coefficients between 92.11 and 101.63%. In the degradation tests conducted for 180 minutes with Lorsban®, the UV/H2O2, photo-Fenton process and photolysis achieved removals at > 99.18, 99.18 and 98.72 % respectively. The same procedures applied to analytical standard chlorpyrifos resulted in degradations of 96.47, 94.34 and 84.92%. Regarding the ecotoxicity tests, the L. sativa seeds showed to be less sensitive to pre and post-treatment samples. Only in one of the samples (Lorsban® after 180 minutes of UV/H2O2) of D. magna occur a reduction in ecotoxicity with a toxicity factor to 16. In all other samples in all dilutions the immobility was greater than 10% with toxicity factor greater than 16. With A. aegypti larvae the toxicity reduction were 26.7, 18.5 and 17% with photolysis, photo-Fenton and UV/H2O2 process, respectively. In analytical standard chlorpyrifos samples there was no reduction of toxicity. The use of light conditions allowed an evaluation of the kinetics of the reactions, reaching high percentages of degradation, however, no significant reductions were observed in the ecotoxicity and larvicidal effect of the analyzed solutions, possibly due to the residual chlorpyrifos concentration, higher than the toxic limits.